Relação da expressividade das proteínas p53 e p16 no carcinoma de células escamosas na cavidade oral, laringe e faringe com a sobrevida: risco ou proteção? - Vidal, Maria Da Graca Caminha [UNIFESP] (2019)
Objectives: To verify the expressiveness of p53 and/or p16 proteins in patients with squamous cell carcinoma in the oral cavity, larynx and pharynx sites. To relate the expressiveness of proteins p53 and/or p16 with staging, lymph node dissemination and survival. To verify whether p53 and/or p16 proteins have a risk or protection aspect in these patients and their relevance to the primary site. Method: The analysis of the expressiveness of p53 and/or p16 proteins was made by immunohistochemistry, by means of an automated system using the Benchmark GX Ventana (Germany) equipment. The neoplastic material used was derived from biopsies or surgical specimens with a confirmed diagnosis of SCC of the oral cavity, larynx and pharynx, of patients diagnosed and treated at the Santa Maria University Hospital in Rio Grande do Sul-Brazil, in the period of January 2014 to January 2018. It is a prospective longitudinal observational study. Statistical Methodology: The Chi-Q test, Wilcoxon test, Kaplan-Meier Estimator (Survival) Cox univariate (occurrence of deaths) and the estimated Log-rank test (comparison between survival curves) were used. The level of significance adopted is 5%. Results: In the oral cavity, the expressiveness of the p53 protein was 69.6% and the p16 protein was 30.4%. In p53 protein, level C was the most expressed in 40.6% and the p16 protein was grade 0 in 69.6%. Patients with positive p53 protein were in stages III and IV (56.3%). Patients with p53 protein had 2.8 times more chances of progression to death from the disease. The p16 protein had the smallest expression in the tongue and/or oral floor (p = 0.014). The highest number of deaths caused by the disease occurred with the patients with the p16 grade 0 protein. Patients with the p16 protein had 0.6 times more chances of death due to the disease. In the larynx, the expressiveness of proteins p53 and p16 was 57% and 29.1%, respectively. There was a higher number of stages III and IV with the p53 protein. The patients with the p53 protein had 2,5 times more chances of evolution to death by the disease. Patients with the p16 protein had 1.17 times more chances of death from the disease. In the pharynx, the expressiveness of p53 protein and p16 protein was 57.1% and 34, 1%, respectively. Most patients were in stage III and IV. Patients with p53 protein had 1.17 times more chances of progression to death from the disease. The p16 protein had its highest expression in T1 tumors (p = 0.046). The isolated p16 protein was more frequent in the oropharynx in 9 (90%) cases. Patients with the p16 protein had 0.83 times more chances of progression to death from the disease. There was no direct relationship with lymph node dissemination, but in its absence, there were more lymphnode metastases. Conclusion: The p53 protein had its highest expressiveness in all sites, with higher frequency in stages III and IV. It was unrelated to lymph node dissemination. It is a risk protein in squamous cell carcinoma of all sites, being more intense in the oral cavity and larynx and lower in the pharynx. The p16 protein had its highest expressiveness in the oropharynx. It is a protein with protective aspect, especially in the oropharynx and oral cavity. The larynx and hypopharynx did not reproduce this profile. The relevance of proteins p53 and p16 in survival was directly related to the primary site of the neoplasm.